Acupuncture for poststroke spasticity: A protocol of a systematic review and meta-analysis. Issue 39 (September 2019) - Shi, Li-hong; Guo, Liu-xue; Zhang, Hui-ling; Li, Yu-xi; Zhong, Dong-ling; Xiao, Qi-wei; Li, Juan; Ye, Xiao-qian; Jin, Rong-jiang
Abstract: Introduction: Spasticity is the most common complication after stroke, which is the main obstacle in the recovery of motor function. Spasticity seriously affects the quality of life and brings a heavy burden to families and society. Acupuncture is an effective method for stroke. However, whether acupuncture is effective for poststroke spasticity is still unknown. The purpose of this systematic review (SR) is to evaluate the effectiveness and safety of acupuncture for poststroke spasticity. Methods and analysis: We will search the following databases from inception to July 2019: China Biology Medicine (CBM), China National Knowledge Infrastructure (CNKI), Wan Fang Data, the Chinese Science and Technology Periodical Database (VIP), PubMed, Embase, The Cochrane Library, and Web of Science. All relevant randomized controlled trials (RCTs) utilizing acupuncture for poststroke spasticity will be included. The primary outcome is the modified Ashworth scale. Secondary outcomes include composite spasticity scale, clinic spasticity index, electromyographic activity, Hoffmann reflex activity, or other spasticity-related outcomes. Study selection, data extraction, and quality assessment will be performed independently by 2 reviewers. Assessment of risk of bias and data synthesis will be conducted using Review Manager V5.3 software. Ethics and dissemination: The ethical approval is not required since SR is based on published studies. The results of this SR will be published in a peer-reviewed scientific journal according to the Preferred Reporting Item for Systematic Review and Meta-analysis (PRISMA) guidelines. PROSPERO registration number: CRD42019129779. Abstract : Supplemental Digital Content is available in the text